Clinical Evaluation of Gingival Biotype and its Association with Age and Gender among Patients Visiting a Tertiary Care Center - Subedi, Suraksha; Ranjit, Rebicca; Bista, Soni (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Gingival biotype is considered as the most important prognostic factor that determines the success of periodontal therapy and somehow affects its outcome. Hence, it is crucial to identify the gingival biotype before dental treatment. This study was carried out to assess the prevalence of gingival biotypes in patients visiting a teaching hospital and evaluate its association with age and gender. Methods This cross-sectional study was conducted from September 2021 to April 2022 amongst 225 participants from department of periodontics, Gandaki Medical College, Pokhara, Nepal. The demographic data of subjects were recorded and their gingival biotype was assessed using the probe transparency technique. Results Among 225 participants, the majority of them (124, 55.11%) exhibited a thick gingival biotype. Thicker gingival biotype was more prevalent among age group 18 to 40 years (65, 69.15%) and greater in males (71, 77.17%) which were statistically significant (p<0.001). Conclusions Thicker gingival biotype was more prevalent among participants in the present study. The assessment of gingival biotype of the patients can provide the knowledge to the clinician about the care to be taken while tissue handling during periodontal therapy. This in turn provides a more favorable tissue environment and maximizes the predictability of periodontal treatment.